2009
DOI: 10.1063/1.3191666
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of piezoelectric properties of high-TC Bi(Mg1/2Ti1/2)O3–PbTiO3

Abstract: The temperature dependence of both polarization and electric-field induced strain was investigated for (1−x)Bi(Mg1/2Ti1/2)O3–xPbTiO3 (x=0.36, 0.37, and 0.38), with the morphotropic phase boundary located at x=0.37. Remanent polarization (Pr) and maximum polarization (Pmax) of all compositions are enhanced with increasing temperature up to 175 °C, which is rationalized as improved domain switching due to reduced tetragonality (c/a). The hysteresis during unipolar electric cycling tends to decrease with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 32 publications
(69 reference statements)
5
76
0
1
Order By: Relevance
“…The enhanced piezoelectric property is due to the fact that domains can be easier switched with the reduced tetragonality as the temperature is raised. 4 For the application of piezoelectric actuators, the electric field induced strain is an important parameter. The strain behavior of the piezoelectric ceramics is related to the crystal structure, domain configuration, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced piezoelectric property is due to the fact that domains can be easier switched with the reduced tetragonality as the temperature is raised. 4 For the application of piezoelectric actuators, the electric field induced strain is an important parameter. The strain behavior of the piezoelectric ceramics is related to the crystal structure, domain configuration, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…23) In the present study, we attempted to grow (111) one-axisoriented films of a high-pressure phase Bi(Mg 1=2 Ti 1=2 )O 3 on (100)Si substrates. Bi(Mg 1=2 Ti 1=2 )O 3 has been investigated as an end member of the piezoelectric materials, 24,25) and it showed good ferroelectricity in the case of (111)-oriented epitaxial films grown on (111) c SrRuO 3 /(111)SrTiO 3 substrates. 19) …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Especially, it was found that the ferroelectric performance of BMT-PT ceramics is enhanced at elevated temperatures, which benefits applications of devices. It is ascribed to improved domain switching mobility which is associated with reduced lattice distortion.…”
Section: à2mentioning
confidence: 99%
“…4 For applications with stability of structure and performance under specific temperature conditions, the search for bismuth-based perovskite ferroelectric materials has stimulated much interest due to the desirable behavior of high T C , such as promising system of BiMeO 3 -PbTiO 3 , where Me could be single trivalent cation (e.g., Sc 3þ , In 3þ , and Fe 3þ ) or a mixed cation combination with an average trivalence (e.g., Zn 1/2 Ti 1/2 and Mg 1/2 Ti 1/2 ). [5][6][7][8][9][10][11][12][13][14][15][16] The improved ferroelectric performances in the BiMeO 3 -PbTiO 3 are ascribed to the strong hybridization between oxygens and A-site Pb/Bi or B-site cations which have a strong ferroelectric activity, such as Ti and Zn. 17,18 Bi substitution plays a unique role in considerable enhancement on both large polarization and high T C .…”
Section: Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation